Perbandingan Busana Arca Harihara Era Klasik Akhir (Koleksi State Hermitage Museum, Museum Nasional Jakarta, dan Balai Lelang Christie’s) - Muthi'ah, Waridah; Sachari, Agus (Institut Seni Indonesia Surakarta, 2021)
Harihara is the amalgamation of two great gods in Hinduism, Siva and Vishnu. During the Late Classical Era (Majapahit period, 13th-15th centuries AD) three deification statues which portrayed the kings as Harihara have been found. Out of these three, two of them are not located in Indonesia anymore, one is part of the collection of Hermitage Museum, St. Petersburg, and one is in Christie’s Auction Gallery. Since these two statues are not widely known, they are barely mentioned or studied in the field of classical archaeology and art. This research focuses on the physical attributes of those two statues, particularly the clothing elements and divine attributes, in comparation to the deification statue of Raden Wijaya as Harihara, which is originated from Candi Simping and now is located in National Museum, Jakarta. The research was conducted using a qualitative-comparative method with iconographic and historical approach. It is found that while these statues show the amalgamation of Siva and Vishnu’s attributes, the depiction of Harihara in those statues are not exactly following Harihara iconography as regulated in the canons of Silpasastra and Manasara. While the canon physical attributes of Shiva and Vishnu side by side equally, in the depiction of Harihara in Java, those attributes are mixed and not always follows a rigid pattern. It is suggested that the depiction of kings as Harihara show an attempt to project them as the unifier of different factions and religious sects. The inequal depiction of Vishnu and Siva’s attributes in king’s deification statues indicates not only the dynamics of the religion in the era, but also as mean to build king’s image in the image of the God.